Strategies for Enhancing Teacher Professionalism Through the Implementation of the Madrasah Principal’s Duties and Responsibilities - Hakin Najili; Supiana Supiana; Mohamad Erihadiana; Suyatman, Ujang (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the strategies employed by madrasah principals to enhance teacher professionalism through the implementation of managerial functions, academic supervision, entrepreneurship, and socio-spiritual leadership at MAN 1 Bandung and MAN 2 Bandung. The study employs a qualitative approach using a descriptive case study method. Data collection techniques included in-depth interviews, participatory observation, and document analysis, while data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that strategies for enhancing teacher professionalism begin with needs-based planning, followed by strengthening clinical academic supervision, fostering a collaborative and innovative work culture, and implementing continuous evaluation. The implementation of these strategies has a positive impact on improving teachers’ pedagogical and professional competencies, work discipline, and the quality of learning. The novelty of this research lies in the discovery of the “Resilient Professionalism” model a model of teacher professionalism that emphasizes resilience and adaptability to changes in curriculum, technology, and educational dynamics. This model is built through the synergy of the spiritual-managerial leadership of the madrasah principal and the collective efficacy of teachers to achieve sustainable quality in Islamic education.